-25G=0

Solo disponible en BuenasTareas
  • Páginas : 2 (424 palabras )
  • Descarga(s) : 0
  • Publicado : 16 de junio de 2011
Leer documento completo
Vista previa del texto
1.- 5 + 6x = 2
2.- 4b + 1 = -18
3.- 18c - 3 = 0
4.- 5 - 2d = 9
5.- - 3f + 1 = 4
6.- - 2 - 5g = 0
7.- 13 - h = 13
8.- 5j - 9 = 3j + 5
9.- 2k + 7 = 12 - 3k
10.- 10 - 4x = 7 - 6x11.- 5m - 3,2 = 2m + 2,8
12.- 5n - 2n + 12 = 35 - 4n - 9
13.- 3ñ - 15 + 2ñ - 14 = ñ - 11
14.- 48p - 13 + 12p = 72p - 3 - 24p
15.- q - 3 + 6q - 9 + 12q - 15 = q
16.- 6r + 12r - 9 - 8r + 10+ r = 0
17.- 5s + (4 - s) = 9 - (s - 6)
18.- (3t - 1) + 7 = 8t - (3 - 2t)
19.- 3 - (8v - 5) + (6 - 7v) - 1 = 7 - (v -1) + (4v + 4)
20.- (3w - 8) - (4 - 9w) + 3 = 7w - 2 - (5w + 9 - 3)21.- -(4x - 6 + 5x) + (9 - 5x + 3 - 2x) = 7x - (1 - 6x)
22.- 12y = 3(3y - 5)
23.- 3z - 1 = 2(z - 1)
24.- 2(b + 2) - 5(2b - 3) = 3
25.- 7 - 6(c - 1) + 3(3 - 4c) = 7 + (7c - 4)
26.- 4 -2(d + 7) - (3d + 5)=2d + (4d - 9 + 3d) - (d - 3)
27.- 8(6f - 14) - 7(12 - 5f) + (23f + 2) - (2f + 65) = 0
28.- 21 - [5g - (3g - 1)] - g = 5g - 12
29.- 40h - [24 - (6h + 8) - (5 - 2h)] = 3 -(8h - 12)
30.- 3[2 - (3j - 6)] + 4[6j - (1 - 2j)] = 4 - 5j
31.- 2 - {k - [6k - (1 - 2k)]} = 100
32.- 3[2x - (5x + 2)] + 1 = 3x - 9(x -3)
33.- 2 - {2m + [2m - (2 - 2m)]} = 2
34.- 34 -52(12n - 34) + 235 = 32 + 101(35n - 1)
35.- 2 - (3ñ + 4) - (5ñ - 6) - (7ñ - 8) - (9ñ - 10) = 11
36.- 2[7p - 2(p - 1)] + 3(4p + 7) = 5 - (p - 1)
37.- 8{2 - [q + 2(q - 3)] + 1} = 3 - (8 -3q)
38.- 2 - 3(r - 7) - 7r = 4(r - 2) + 8
39.- 33,7 - (1,5s + 2,3) = 3,4s - (0,4 - 5,7s)
40.- (t - 3) ² - (t - 2) ² = 5
41.- (2v - 4) ² + 6.v - 3 = 4.v ² - (3.v - 1)
42.- (w + 3) ² + 4 =(w - 2) ² + 5w - 2
43.- (3x - 3) ² - (2x - 7) = (3x - 5)(3x + 5)
44.- 2 - (y + 1) ² = 5 - 3[y - (5y + 9)] - y ²
45.- 6z - 1 + 2z + 5z - 9 - 234 = 999
46.- 2{x - [x - (x - 1)]} + (x + 2)= 256
47.- (x - 7) ² - (1 + x) ² = 2(3x - 4)
48.- 6x - (2x - 1)(2x + 1) = 2 - (3 + 2x) ²
49.- 7 - [8x - 3(x + 3)] = 5x - (4 - 2x)
50.- 1 - a = 1
51.- b/5 = 1/2
52.- 2.c/7 = 3/4
tracking img